Magnetic Grüneisen parameter for model systems - Gomes, Gabriel O. [UNESP]; Squillante, Lucas [UNESP]; Seridonio, A. C. [UNESP]; Ney, Andreas; Lagos, Roberto E. [UNESP]; De Souza, Mariano [UNESP] (American Physical Society (APS), 2019)
The magnetocaloric effect (MCE), which is the refrigeration based on the variation of the magnetic entropy, is of great interest in both technological applications and fundamental research. The MCE is quantified by the magnetic Grüneisen parameter Γmag. We report on an analysis of Γmag for the classical Brillouin-like paramagnet for a modified Brillouin function taking into account a zero-field splitting originated from the spin-orbit (SO) interaction and for the one-dimensional Ising (1DI) model under a longitudinal field. For the Brillouin-like model with SO interaction and the longitudinal 1DI model, a sign-change in the MCE is observed for vanishing T and B. SO interaction leads to a narrowing of the enhancement of Γmag for T and B→0. Our findings emphasize the relevance of Γmag for exploring critical points. Also, we show that the Brillouin model with and without SO interaction can be recovered from the 1DI model in the regime of high temperatures and vanishing coupling constant J.